The concept of the intellect according to Nuruddin Al-Raniri in the Bustan Al-Salatin - Noor Muhammad, Salmah Jan (Dewan Bahasa dan Pustaka, 2022)
Written by Nuruddin al-Raniri, Bustan al-Salatin ranks among the most well-known pieces of traditional Malay literature. This work discusses issues of varying themes, such as religion, politics, customs and culture, in order for a kingdom to function and as a guide for the rulers of a kingdom.Â One of the issues discussed in the Bustan al-Salatin concerns the intellect. The intellect is the highest gift awarded by Allah to humankind. Therefore, Nuruddin al-Raniri deals at length with this and uses several sources as references to strengthen his argument. The present article will focus on two objectives that is, to identify the concept of the intellect in the manuscript, and to analyse the categories which al-Raniri divides the intellect as in his Bustan al-Salatin. Library research and content analysis was employed to achieve this. Early findings show that there are several categories into which al-Raniri divides the intellect in Bustan al-Salatin, namely: understanding, function, position, the different categories of the intellect and the ideal life through the use of the intellect. The content of this manuscript is not only aimed at giving rulers direction but also to educate the community to become servants of Allah who know their Creator.